Serotonergic Modulation of Neuronal Activity in the Nucleus Accumbens Following Repeated Methamphetamine Administration in Rats - Kumatoshi Ishihara; Naomichi Takahashi; Naoki Komoto; Chisato Yoshikawa; Shuhei Fukumoto; Soichiro Ide; Takeshi Kimura; Koichiro Ozawa (Elsevier, 2013)
Electrophysiological studies were performed to determine whether serotonergic modulation in the nucleus accumbens (NAcc) was affected after repeated methamphetamine (MAP) administration. NAcc slices (400 μm) from Wistar rats administered MAP (5 mg/kg) or saline once daily for 5 days were prepared 1, 5, or 10 days after the final injection. Population spikes (PS) induced by local stimulation of NAcc were recorded. PS inhibition by serotonin was significantly attenuated in the MAP group at 5 days but did not differ at 1 or 10 days. We next analyzed the effects of serotonin receptor subtype (5-HT1A,2,3,4,6,7)-selective agonists of PS. Differences between saline and MAP groups in 5-HT1A,2,3,4,6 receptor agonist-induced changes of PS were small or not significant. Interestingly, 5-HT7 receptor agonists significantly enhanced PS in the MAP group. Changes in the secondary messenger system related to 5-HT7 receptors were also investigated. Adenylate cyclase activator-induced PS enhancements were significantly larger in the MAP group. However, dibutyryl-cAMP-induced PS enhancement was not significantly different. In conclusion, 5-HT-induced inhibition of PS in NAcc was attenuated 5 days after repeated MAP treatment: the change in the effect of 5-HT was probably due to enhancement of the excitatory modulation via the 5-HT7 receptor with adenylate cyclase signal transduction systems. [Supplementary Figure: available only at http://dx.doi.org/10.1254/jphs.13100FP] Keywords:: methamphetamine, nucleus accumbens, serotonin, population spike, adenylate cyclase